IMPROVING MATHEMATICS LEARNING ACTIVITIES AND RESULTS THROUGH REACT LEARNING STRATEGIES IN STUDENTS OF CLASS X-MIPA-1 SMA NEGERI 2 BLORA - Mutakin (Literasi Nusantara, 2021)
The purpose of this study is to increase the activity and learning outcomes of class students X-MIPA-1 SMA Negeri 2 Blora, Blora Regency for the academic year 2019/2020 to learn mathematics on Logarithmic material through contextual learning with the REACT strategy (Relating, Experiencing, Applying, Cooperating and Transferring). This research is a classroom action research. There are three cycles in this study, where the results of one cycle become a reflection material to make improvements to the implementation of learning in the next cycle. To get the research data used formative tests, observation sheets and interviews. The research subjects were students of class X-MIPA-1 SMA Negeri 2 Blora which consisted of 35 students. Data analysis was carried out quantitatively with the benchmark of achievement of student learning outcomes classically 75%, and qualitatively for learning activities. The results of observations on student activity between cycles 1 and 2 increased by 20.7% and between cycles 2 and 3 increased 9.3%. The results showed that the percentage of mastery learning outcomes obtained from formative tests in the first cycle was 57.1%, in the second cycle 71.4% and in the third cycle 85.7%. From the results of the interviews, it is known that most of the students enjoy group learning with this strategy. In this study, it can be concluded that the REACT strategy can increase the activity and learning outcomes of students in class X-MIPA-1 SMA Negeri 2 Blora.